A Case of Old Age-Onset Generalized Pustular Psoriasis with a Deficiency of IL-36RN (DITRA) Treated by Granulocyte and Monocyte Apheresis - Chiharu Tominaga; Masaaki Yamamoto; Yasutomo Imai; Kiyofumi Yamanishi (Karger Publishers, 2015)
A 78-year-old woman who had been suffering from psoriasis vulgaris for 31 years was admitted to hospital because of her erythroderma. A toxic eruption was suspected and she was treated with prednisolone 30 mg daily. However, it was ineffective and, suspecting psoriatic erythroderma, cyclosporine 150 mg daily was administered with tapering of the prednisolone. Two weeks after a dose reduction of cyclosporine to 100 mg/day, erythroderma with widespread generalized pustules and fever developed. Histology of a biopsy revealed inflammatory infiltrates in the skin with a spongiform pustule of Kogoj, which was consistent with generalized pustular psoriasis (GPP). Her pustules improved with additional etretinate 20 mg/day, but the erythroderma persisted and she consulted us. Three sessions of granulocyte and monocyte apheresis once weekly were effective for her condition and decreased her serum levels of IL-6 and IL-8. She had homozygous mutations of c.[28C>T] in IL36RN which cause p.[Arg10Ter]. She is the oldest reported case of GPP with a deficiency of interleukin-36 receptor antagonist (DITRA), although GPP in DITRA has been suggested to usually occur in younger cases with no pre-existing psoriasis vulgaris.